Impact of Oxbow Lakes Project II on participant households - Ahmed, Dilruba; Hossain, Altaf; Mustafa, Shams (BRAC, 2019)
The Oxbow Lakes Small Scale Fishermen Development Project Phase II (OLP-11) is being financed jointly by International Fund for Agricultural Development (IF AD), Danish International Development Assistance (DANIDA), World Food Programme (WFP), Government of Bangladesh (GoB) and implemented jointly by Project Implementation Unit (PIU) of GoB, Directorate of Fisheries (DoF), DANIDA and BRAC since June 1991. BRAC is entrusted with organizing the fishermen at the grassroots level, capacity development of the fishermen through management and skill training, credit support, and raising of productivity through extension of technical services to improve the condition of the rural poor fishermen in particular, and to eradicate rural poverty, in general This study focuses on the impact of the Second Oxbow Lake Project (OLP II) on participant fishermen households. The objective of the study is to provide the analysis of the changes in the material well-being of the participant households and to discuss the changes in the lives of the non-participants of the oxbow lake catchment areas as a result of OLP II intervention The study gathered data through survey in 1993 and resurvey in 1995 from 1189 participant and non-participant households of 21 oxbow lake catchment areas. The households were randomly selected for conducting survey. Both participants and non-participants are the members of BRAC's Rural Development Programme (RDP). To find out the displaced fishermen household due to the OLP II intervention and to know their economic condition the study also included case study in 3 oxbow lake catchment areas. Positive changes have taken place in the oxbow lake catchment areas as a result of the fishermen's participation in the OLP !i. These changes have been categorized into two broad areas, i.e., material well-being of the participant households as well as the indirect impact of the OLP on the inhabitants of the oxbow lake catchment areas and displacement caused by the project. According to the findings the shelter environment in terms of electricity facility and sanitation of the participant households has improved compared to that of the non-participant households.